Konsep Akhlak Tasawuf sebagai Fondasi Etika Bisnis Syariah - Ahmad, Diki; Kamaludin, Amal Kamaludin (Ma'soem University, 2025)
The concept of akhlaq tasawuf holds a central role in shaping the foundation of Islamic business ethics, which is not only oriented toward legal compliance but also toward spiritual depth and the moral integrity of entrepreneurs. This article aims to critically examine the relationship between ethical values in the Sufi tradition—such as honesty (?idq), trustworthiness (amanah), asceticism (zuhud), and excellence (ihsan)—and the principles of Islamic business ethics that emphasize justice, transparency, and blessing (barakah). This study employs a qualitative approach based on literature review and conceptual analysis. It finds that akhlaq tasawuf can serve as a transformative foundation in building a business culture oriented toward maq??id al-shar?‘ah and collective welfare.. The integration of spirituality and economic practice opens space for a model of Islamic business that is not only economically competitive but also contributes to the moral and social development of the community. This study recommends strengthening Sufi-based ethical education within the Islamic economics curriculum as well as applying spiritual values in the institutional policies of Islamic business.